Livestock phenomics and genetic evaluation approaches in Africa: current state and future perspectives - Houaga, Isidore; Mrode, Raphael; Opoola, Oluyinka; Chagunda, Mizeck G. G.; Mwai, Okeyo A.; Rege, John E. O.; Olori, Victor E.; Nash, Oyekanmi; Banga, Cuthbert B.; Okeno, Tobias O.; Djikeng, Appolinaire (Frontiers in Genetics, 2023)
The African livestock sector plays a key role in improving the livelihoods of people through the supply of food, improved nutrition and consequently health. However, its impact on the economy of the people and contribution to national GDP is highly variable and generally below its potential. This study was conducted to assess the current state of livestock phenomics and genetic evaluation methods being used across the continent, the main challenges, and to demonstrate the effects of various genetic models on the accuracy and rate of genetic gain that could be achieved. An online survey of livestock experts, academics, scientists, national focal points for animal genetic resources, policy makers, extension agents and animal breeding industry was conducted in 38 African countries. The results revealed i) limited national livestock identification and data recording systems , ii) limited data on livestock production and health traits and genomic information, iii) mass selection was the common method used for genetic improvement with very limited application of genetic and genomic-based selection and evaluation, iv) limited human capacity, infrastructure, and funding for livestock genetic improvement programmes, as well as enabling animal breeding policies. A joint genetic evaluation of Holstein-Friesian using pooled data from Kenya and South Africa was piloted. The pilot analysis yielded higher accuracy of prediction of breeding values, pointing to possibility of higher genetic gains that could be achieved and demonstrating the potential power of multi-country evaluations: Kenya benefited on the 305-days milk yield and the age at first calving and South Africa on the age at first calving and the first calving interval. The findings from this study will help in developing harmonized protocols for animal identification, livestock data recording, and genetic evaluations (both national and across-countries) as well as in designing subsequent capacity building and training programmes for animal breeders and livestock farmers in Africa. National governments need to put in place enabling policies, the necessary infrastructure and funding for national and across country collaborations for a joint genetic evaluation which will revolutionize the livestock genetic improvement in Africa.